Performance of clinical scoring and microscopic combinations for diagnosing pulmonary tuberculosis with the GenXpert criteria - L. Susanti, Anita; T. Khairunnisa, Anindita; Firdaus, Firman; K. P. Dewi, Ania; Ratunanda, Susanti; Anggraeny, Dian (ACTA Medical Health Sciences, 2023)
Pulmonary tuberculosis is a prominent health issue in Indonesia, which ranks second in the world regarding the number of patients. Rapid tuberculosis detection is crucial for early treatment, a better prognosis, and a reduction in disease transmission; however, the availability of molecular rapid tests is limited. Cross-sectional design and retrospective analyses of pre-pandemic data from 723 patients with suspected pulmonary tuberculosis from 2017 to 2019 were conducted in this study. The study aimed to assess the performance of clinical scoring and microscopic examination in tuberculosis diagnosis at RSUD Sayang Cianjur. The effectiveness of sequential (two-stage) and simultaneous combinations of clinical scoring and sputum smear microscopic were investigated. Performance assessments consisted of 2x2 tables, calculation according to Gordis, and Receiver Operator Characteristic (ROC) analysis, with GenXpert results as the gold standard. The results showed lower performance of the individually performed scoring system, with clinical scoring having a sensitivity of 34.44% and a specificity of 97.15%. Microscopic Acid Fast Bacteria (AFB) had a sensitivity of 70.20% and a specificity of 98.57%. The net sensitivity of the sequential combination was 28.48%, and the specificity was 99.05%. The net sensitivity of the simultaneous combination was 77.15%, and the specificity was 95.72%. The area under the curve from the sequential diagnostic method was 0.728, and the area under the curve of the simultaneous diagnostic was 0.884. The sequential and simultaneous combinations of clinical scoring and the AFB microscopy improved the test performance. The simultaneous combination performed slightly better than the sequential combination. DOI : 10.35990/amhs.v2n2.p63-72 REFERENCE Bagcchi S. WHO's Global Tuberculosis Report 2022. Lancet Microbe. 2023;4(1):e20. Pandey D, Yadav A. Efficacy of Gene Xpert over other diagnostic modalities of tuberculosis among children. Int J Contemp Pediatr. 2019;6(4):1545–51. Shi J, Dong W, Ma Y, Liang Q, Shang Y, Wang F, et al. GeneXpert MTB/RIF Outperforms Mycobacterial Culture in Detecting Mycobacterium tuberculosis from Salivary Sputum. Biomed Res Int. 2018;2018:1514381. Mechal Y, Benaissa E, El Mrimar N, Benlahlou Y, Bssaibis F, Zegmout A, et al. Evaluation of GeneXpert MTB/RIF system performances in the diagnosis of extrapulmonary tuberculosis. BMC Infect Dis. 2019;19(1):1069. Mukhida S, Vyawahare CR, Mirza SB, Gandham NR, Khan S, Kannuri S, et al. Role of GeneXpert MTB/RIF assay for the diagnosis of cervical lymph node tuberculosis and rifampicin resistance. Tzu Chi Med J. 2022;34(4):418–22. Vassall A, Siapka M, Foster N, Cunnama L, Ramma L, Fielding K, et al. Cost-effectiveness of Xpert MTB/RIF for tuberculosis diagnosis in South Africa: a real-world cost analysis and economic evaluation. Lancet Glob Health. 2017;5(7):e710–9. Khumsri J, Hanvoravongchai P, Hiransuthikul N, Chuchottaworn C. Cost-Effectiveness Analysis of Xpert MTB/RIF for Multi-Outcomes of Patients With Presumptive Pulmonary Tuberculosis in Thailand. Value Health Reg Issues. 2020;21:264–71. World Health Organization. Automated Real-Time Nucleic Acid Amplification Technology for Rapid and Simultaneous Detection of Tuberculosis and Rifampicin Resistance: Xpert MTB/RIF Assay for the Diagnosis of Pulmonary and Extrapulmonary TB in Adults and Children: Policy Update. Geneva: WHO; 2013. Chakraborty A, Ramaswamy S, Shivananjiah AJ, Puttaswamy RB, Chikkavenkatappa N. The role of GeneXpert in the diagnosis of tubercular pleural effusion in India. Adv Respir Med. 2019;87(5):276–80. Directorate General of Prevention and Disease Control. Tuberculosis Control in Indonesia 2022. Jakarta: Ministry of Health Republic of Indonesia; 2022. Gurung SC, Dixit K, Rai B, Dhital R, Paudel PR, Acharya S, et al. Comparative Yield of Tuberculosis during Active Case Finding Using GeneXpert or Smear Microscopy for Diagnostic Testing in Nepal: A Cross-Sectional Study. Trop Med Infect Dis. 2021;6(2). Agrawal M, Bajaj A, Bhatia V, Dutt S. Comparative Study of GeneXpert with ZN Stain and Culture in Samples of Suspected Pulmonary Tuberculosis. J Clin Diagn Res. 2016;10(5):DC09–12. Agizew T, Boyd R, Auld AF, Payton L, Pals SL, Lekone P, et al. Treatment outcomes, diagnostic and therapeutic impact: Xpert vs. smear. A systematic review and meta-analysis. Int J Tuberc Lung Dis. 2019;23(1):82–92. Orlando S, Triulzi I, Ciccacci F, Palla I, Palombi L, Marazzi MC, et al. Delayed diagnosis and treatment of tuberculosis in HIV+ patients in Mozambique: A cost-effectiveness analysis of screening protocols. PLoS One. 2018;13(7):e0200523. Subuh M, Priohutomo S, Widaningrum C. Pedoman Nasional Pengendalian Tuberkulosis. Dinihari TN, Siagian V, editors. Jakarta: Direktorat Jenderal Pengendalian Penyakit dan Penyehatan Lingkungan, Kemenkes RI; 2014. Baik Y, Rickman HM, Hanrahan CF, Mmolawa L, Kitonsa PJ, Sewelana T, et al. A clinical score for identifying active tuberculosis while awaiting microbiological results: Development and validation of a multivariable prediction model in sub-Saharan Africa. PLoS Med. 2020;17(11):e1003420. Hanifa Y, Fielding KL, Chihota VN, Adonis L, Charalambous S, Foster N, et al. A clinical scoring system to prioritise investigation for tuberculosis among adults attending HIV clinics in South Africa. PLoS One. 2017;12(8):e0181519. Balcha TT, Skogmar S, Sturegard E, Schon T, Winqvist N, Reepalu A, et al. A Clinical Scoring Algorithm for Determination of the Risk of Tuberculosis in HIV-Infected Adults: A Cohort Study Performed at Ethiopian Health Centers. Open Forum Infect Dis. 2014;1(3):ofu095. Zimba O, Tamuhla T, Basotli J, Letsibogo G, Pals S, Mathebula U, et al. The effect of sputum quality and volume on the yield of bacteriologically-confirmed TB by Xpert MTB/RIF and smear. Pan Afr Med J. 2019;33:110. Gordis L. Epidemiology. 5th ed. Philadelphia: Elsevier Saunders; 2014. Nahm FS. Receiver operating characteristic curve: overview and practical use for clinicians. Korean J Anesthesiol. 2022;75(1):25–36.